Muscle thickness correlates to muscle cross sectional area in the assessment of strength training induced hypertrophy - Franchi, Martino V.; Longo, Stefano; Mallinson, Joanne E.; Quinlan, Jonathan I.; Taylor, Tariq; Greenhaff, Paul L.; Narici, Marco V. (Wiley, 2017)
Aim: Muscle thickness (MT) measured by ultrasound has been used to estimate cross-sectional area (measured by CT and MRI) at a single time-point. We tested whether MT could be used as a valid marker of MRI determined muscle anatomical cross-sectional area (ACSA) and volume changes following resistance training (RT). Methods: Nine healthy, young, male volunteers (24±2 y.o., BMI 24.1±2.8 kg/m2) had vastus lateralis (VL) muscle volume (VOL) and ACSA mid (at 50% of femur length, FL) assessed by MRI, and VL MT measured by ultrasound at 50% FL. Measurements were taken at baseline and after 12 weeks of isokinetic RT. Differences between baseline and post-training were assessed by Student’s paired t-test. The relationships between MRI and ultrasound measurements were tested by Pearson’s correlation. Results: After RT, MT increased by 7.5±6.1% (p<0.001), ACSAmid by 5.2±5% (p<0.001) and VOL by 5.0±6.9% (p<0.05) (values: means±S.D.). Positive correlations were found, at baseline and 12 weeks, between MT and ACSAmid (r=0.82, p<0.001 and r=0.73, p<0.001, respectively), and between MT and VOL (r=0.76, p < 0.001 and r=0.73, p < 0.001, respectively). The % change in MT with training was correlated with % change in ACSAmid (r=0.69, p = 0.01), but not % change in VOL (r= 0.33, p>0.05). Conclusions: These data support evidence that MT is a reliable index of muscle ACSAmid and VOL at a single time-point. MT changes following RT are associated with parallel changes in muscle ACSAmid but not with the changes in VOL, highlighting the impact of RT on regional hypertrophy.